2022
DOI: 10.2337/db22-0252
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping of Multiple Traits Identifies Novel Genes for Adiposity, Lipids, and Insulin Secretory Capacity in Outbred Rats

Abstract: Despite the successes of human genome-wide association studies, the causal genes underlying most metabolic traits remain unclear. We used outbred heterogeneous stock (HS) rats, coupled with expression data and mediation analysis, to identify quantitative trait loci (QTLs) and candidate gene mediators for adiposity, glucose tolerance, serum lipids, and other metabolic traits. Physiological traits were measured in 1519 male HS rats, with liver and adipose transcriptomes measured in over 410 rats. Genotypes were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The current work supports previous ndings (4,5) by showing that diet-induced obese mice versus chow-fed lean mice had increased GRK5 mRNA levels (~ 2 fold) in white, but not in brown adipose tissue (Fig. 1A-B).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current work supports previous ndings (4,5) by showing that diet-induced obese mice versus chow-fed lean mice had increased GRK5 mRNA levels (~ 2 fold) in white, but not in brown adipose tissue (Fig. 1A-B).…”
Section: Discussionsupporting
confidence: 92%
“…Adipose tissue plays a central role in obesity resulting in adipocyte hyperplasia (increased adipocyte number) and/or adipocyte hypertrophy (increased adipocyte size), although the underlying causes of adipose tissue expansion are generally unknown. Our previous work identi ed G protein-coupled receptor (GPCR) kinase 5 (GRK5) as a candidate causal gene for visceral adiposity, where Grk5 expression positively correlated with retroperitoneal and epididymal white fat pad mass in rats (4) and Grk5 knock-down in 3T3L1 preadipocytes led to decreased total triacylglycerol (TAG) accumulation in mature adipocytes (4). In humans, GRK5 gene expression in white subcutaneous white adipose tissue is positively correlated with BMI (kg/m 2 ) in the African American Genetics of Metabolism and Expression (AAGMEx) cohort (r = 0.22, p = 0.0003), a group of 256 African Americans with in depth glucometabolic phenotyping and adipose tissue transcriptome analysis (5).…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, Krtcap3 was first identified as a potential adiposity gene through GWAS analyses [10][11][12]18] and we confirmed in vivo that decreased expression of Krtcap3 led to increased adiposity [13]. We sought here to repeat the in vivo study with additional metabolic phenotyping and tissue collection in order to better understand the function of Krtcap3 in adiposity, but failed to replicate our results.…”
Section: A Change In Environment and Circulating Cort Levels May Have...mentioning
confidence: 66%
“…Like previous cis -eQTL analyses, these eVariants were predominantly located within +/-400 kB of the TSS of their respective eGene ( Fig S5B ). A comparison with existing rat cis -eQTL databases (RatGTEx: 55,56 , Mitchell et al, unpublished ; and Telese et al, unpublished ), Fig S5C, indicated that most hippocampal eGenes were also significant eGenes within at least four other tissues (out of 11 tissues characterized, Fig S5D ), and confirmed that previously-identified brain cis -eQTLs showed a similar direction of effect on gene expression within the hippocampus (R=0.67-0.75, rho=0.65-0.77, Fig S7-S8 ) when there was at least a nominal ( p <0.05) relationship in our dataset, although many cis -eQTLs remained region specific. As our hippocampal cis -eQTL database represents a valuable resource for the interpretation of rat genomic results, we have shared it on RatGTEx (https://ratgtex.org/download/study-data/#HPC_F2).…”
Section: Resultsmentioning
confidence: 99%